PENGEMBANGAN E-MODUL INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN SCIENTIFIC REASONING PADA PEMBELAJARAN IPA SISWA SMP - Ayu Nurjannah; Rusdianto; Nuha, Ulin (Jurnal Muara Pendidikan, 2025)
The scientific reasoning ability of students in Indonesia was relatively low due to a lack of understanding of the material and learning concepts. Therefore, an interesting learning system was needed and supported by effective media in conveying messages and learning objectives, which facilitated teachers in the teaching process, such as the use of interactive e-modules. This study aimed to develop interactive e-modules to improve scientific reasoning abilities in junior high school science learning. This interactive e-module was developed using the ADDIE model. The results of the study showed a validity percentage of 92.62% (very valid), practicality of 89.51% (practical), and N-gain of 0.59 (medium), while student responses reached 87.18% (very good). Interactive e-modules met the criteria for validity, practicality, and effectiveness because they were arranged systematically and covered all indicators of scientific reasoning abilities. Thus, interactive e-modules were feasible to be implemented as learning media to improve junior high school students' scientific reasoning abilities.